2019
DOI: 10.1038/s41598-019-52332-0
|View full text |Cite
|
Sign up to set email alerts
|

Childhood growth hormone treatment in women with Turner syndrome - benefits and adverse effects

Abstract: Turner syndrome (TS) is characterized by the partial or complete loss of one sex chromosome and results in growth failure, gonadal insufficiency and cardiac anomalies. Treatment with growth hormone (GH) during childhood has indisputable benefits when taking into account the low stature of TS women. Medical records and biochemical findings of 33 TS women treated with GH in childhood (GH+) were compared to those of 124 TS women who did not receive GH (GH−). It seems that the GH-treated group might have had a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
(37 reference statements)
1
26
0
Order By: Relevance
“…However, they also had low thrombocyte counts, a greater prevalence of retrognatism, nail anomalies and elevated creatinine levels, especially when the GH treatment was delayed or prolonged. They concluded that GH treatment in children with TS has benefits in adulthood but adverse effects may occur, especially in girls with treatment that is delayed or is too long [63].…”
Section: Ghd In the Context Of Genetic Disordersmentioning
confidence: 99%
“…However, they also had low thrombocyte counts, a greater prevalence of retrognatism, nail anomalies and elevated creatinine levels, especially when the GH treatment was delayed or prolonged. They concluded that GH treatment in children with TS has benefits in adulthood but adverse effects may occur, especially in girls with treatment that is delayed or is too long [63].…”
Section: Ghd In the Context Of Genetic Disordersmentioning
confidence: 99%
“…The international guidelines (4) recommend initiation of hormone replacement therapy (HRT) between 11-12 years of age. Soriano-Guillen et al (18) report of age at start of HRT between 14.6 and 16 years of age, while Irzyniec et al (19) start HRT between 8 and 14 years of age. Published Bulgarian data from Stefanova et al for the treatment of TS children documented starting of HRT at the age of 13.5-15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, earlier and proper treatment with GH at higher dose can improve growth better [9]. Childhood GH treatment also has bene cial effect on lipid pro le and cardiovascular diseases in women with TS [10].…”
Section: Introductionmentioning
confidence: 99%